Legal needs of adults with life-limiting illness: what are they and how are they managed? A qualitative multiagency stakeholder exercise. Issue 1 (3rd September 2020) - Hawkins, Colette; Kirby, Margaret; Genn, Hazel; Close, Helen
Abstract : Objective: Little is known about legal needs in the context of life-limiting illness, particularly the need for advice concerning legal arrangements, rights and entitlements. This UK-based multiagency stakeholder engagement exercise scoped legal needs associated with life-limiting illness and identified support structures, gaps and opportunities for practice improvement. Method and analysis: Snowball sampling generated a stakeholder group from a wide range of regional and national organisations involved in care of people with life-limiting illness, spanning health, social care, legal support, advice, charities, prison services as well as patient and carer representatives. A coproduced survey of three open questions generated qualitative data, interpreted by thematic analysis. Results: Stakeholders reported a broad spectrum of problems and needs raising legal issues, with no consistency of definition. A classification is proposed, identifying matters concerning rights and entitlements of patients/carers in day-to-day life and decisions around care, both immediate and in the future, as well as professional responsibilities in delivering personalised care. The support structures identified were predominantly online literature, although there was some availability of remote and face-to-face services. Limited awareness of the issues, variable service configuration, fragmentation of care and inequitable access were identified as barriers to support. Stakeholders recognised the need for education and closer multiagency working. Conclusions: 'Legal needs' incorporate wide-ranging issues, but there is inconsistency in perceptions among stakeholders. Practice is variable, risking unmet need. Opportunities for improvement include more formal integration of social welfare legal services in the health context, generating clearer pathways for assessment and management.